Polyphenolic compounds in date fruit seed (Phoenix dactylifera): characterisation and quantification by using UPLC‐DAD‐ESI‐MS. (22nd October 2013) - Habib, Hosam M; Platat, Carine; Meudec, Emmanuelle; Cheynier, Veronique; Ibrahim, Wissam H
Abstract Background Date fruit seeds have been demonstrated to possess high antioxidant activities due to their high content of flavonoids and phenolic compounds. The objective of this work was to identify and quantify the phenolic composition of date seeds. Methods Two UPLC‐DAD‐ESI‐MS analyses were performed on the seed of the Khalas variety as follows: (1) an analysis of simple phenolic compounds [phenolic acids, hydroxycinnamic acids, flavonols, flavones, flavan‐3‐ols (monomers, dimers and trimers)]; and (2) an analysis of all flavan‐3‐ols (monomers, and proanthocyanidin oligomers and polymers) after depolymerisation. Results The amount of total phenolic compounds before depolymerisation was found to be 2.194 ± 0.040 g kg−1 date seed. The analysis of flavan‐3‐ol monomers and constitutive units of proanthocyanidins after depolymerisation revealed 50.180 ± 1.360 g kg−1 flavan‐3‐ols with 46.800 ± 1.012 g kg−1 epicatechin and 3.380 ± 0.349 g kg−1 catechin. Conclusion The results indicate that date seeds are a very rich source of bioactive compounds, thus constituting strong candidates for functional food additives and nutraceuticals. © 2013 Society of Chemical Industry